Experimental investigation of bubble activity at an early stage using te acoustic emission technique in two-phase flow systems. - Alhashan, Taihiret (Cranfield University, 2018)
This thesis presents an experimental investigation and identifies the feasibility of the use of AE technology to detect and monitor both early stage bubble occurrence and throughout the boiling process. The research programme also included monitoring of bubble formation/collapse phenomena in ball and globe valves using AE techniques. It was demonstrated that an AE piezoelectric sensor can detect pressure pulses associated with bubble occurrence during pool boiling and cavitation in flow through valves. For the pool boiling test, a dedicated test-rig was used to diagnose and monitor bubble formation. It was concluded that bubble occurrence is detectable with AE techniques and there is a clear relationship between increasing AE levels and bubble formation during the boiling process. For the valve tests, a purpose-built test-rig was used to monitor and detect cavitation phenomena with various flow rates and different valve opening percentages. It was shown that AE will detect incipient cavitation and that there is a clear correlation between AE signal levels and the flow rate through the ball and globe valves at a constant opening percentage. This investigation successfully demonstrated that AE monitoring is capable of early diagnosis and monitoring of bubble formation phenomena in boiling processes and valves. This research developed a methodology and prototype framework for using the AE technique for detection and diagnosis of early bubble formation and collapse, allowing cavitation development to be tracked, and maintenance activity to be planned to maximise equipment life and minimise downtime.
Keywords: Acoustic emission; bubble occurrence; pool boiling; valves; AE piezoelectric sensor; incipient cavitation